Magnetic/NIR-responsive drug carrier, multicolor cell imaging, and enhanced photothermal therapy of gold capped magnetite-fluorescent carbon hybrid nanoparticles. Issue 17 (9th April 2015) - Wang, Hui; Cao, Guixin; Gai, Zheng; Hong, Kunlun; Banerjee, Probal; Zhou, Shuiqin
Abstract : Multifunctional hybrid nanoparticles have been developed for biomedical applications, including magnetic/NIR-responsive drug release, multicolor cell imaging, and enhanced photothermal therapy. Abstract : This paper reports a type of multifunctional hybrid nanoparticle (NP) composed of gold nanocrystals coated on and/or embedded in a magnetite-fluorescent porous carbon core–shell NP template (Fe3 O4 @PC-CDs-Au) for biomedical applications, including magnetic/NIR-responsive drug release, multicolor cell imaging, and enhanced photothermal therapy. The synthesis of the Fe3 O4 @PC-CDs-Au NPs firstly involves the preparation of core–shell template NPs with magnetite nanocrystals clustered in the cores and fluorescent carbon dots (CDs) embedded in a porous carbon shell, followed by an in situ reduction of silver ions (Ag + ) loaded in the porous carbon shell and a subsequent replacement of Ag NPs with Au NPs through a galvanic replacement reaction using HAuCl4 as a precursor. The Fe3 O4 @PC-CDs-Au NPs can enter the intracellular region and light up mouse melanoma B16F10 cells in multicolor mode. The porous carbon shell, anchored with hydrophilic hydroxyl/carboxyl groups, endows the Fe3 O4 @PC-CDs-Au NPs with excellent stability in the aqueous phase and a high loading capacity (719 mg g −1 ) for the anti-cancer drug doxorubicin (DOX). The superparamagnetic Fe3 O4 @PC-CDs-Au NPs with a saturation magnetization of 23.26 emu g −1 produce localized heat under an alternating magnetic field, which triggers the release of the loaded drug. The combined photothermal effects of the Au nanocrystals and the CDs on/in the carbon shell can not only regulate the release rate of the loaded drug, but also efficiently kill tumor cells under NIR irradiation. Benefitting from their excellent optical properties, their magnetic field and NIR light-responsive drug release capabilities and their enhanced photothermal effect, such nanostructured Fe3 O4 @PC-CDs-Au hybrid NPs are very promising for simultaneous imaging diagnostics and high efficacy therapy.